Regulation of epithelial chloride transport by tyrosine phosphorylation - Loureiro, Cláudia (2017)
Background: Chloride transport proteins are involved in a variety of human diseases and thus represent important drug targets. They are regulated in part through the amount present at the plasma membrane and tyrosine phosphorylation has been described as a novel regulator.